The beneficial roles of apelin-13/APJ system in cerebral ischemia: Pathogenesis and therapeutic strategies - Li, Jiabin; Chen, Zhang; Chen, Jingyu; Yu, Yue (Frontiers in Pharmacology, 2022)
The incidence of cerebral ischemia has increased in the past decades, and the high fatality and disability rates seriously affect human health. Apelin is a bioactive peptide and the ligand of the G protein-coupled receptor APJ. Both are ubiquitously expressed in the peripheral and central nervous systems, and regulate various physiological and pathological process in the cardiovascular, nervous and endocrine systems. Apelin-13 is one of the subtypes of apelin, and the apelin-13/APJ signaling pathway protects against cerebral ischemia by promoting angiogenesis, inhibiting excitotoxicity and stabilizing atherosclerotic plaques. In this review, we have discussed the role of apelin-13 in the regulation of cerebral ischemia and the underlying mechanisms, along with the therapeutic potential of the apelin-13/APJ signaling pathway in cerebral ischemia.